Tomato and tuna: a test for language-free assessment of action understanding - Danek, Amory H.; Gade, Miriam; Lunardelli, Alberta; Rumiati, Raffaella I. (Cognitive and behavioral neurology, 2013)
Objective: We introduce a novel test that allows pictorial, nonverbal assessment of action understanding. - Background: Focusing on action goals and the sequential nature of actions, the “Tomato and Tuna Test” tests whether exposure to the accomplished goal of an action is sufficient to infer the preceding action. This aspect has rarely been addressed in conventional paradigms. - Methods: We used the Tomato and Tuna Test in conjunction with another task, the Kissing and Dancing Test, to detect action understanding deficits in 11 patients (mean age 72±6 years) with chronic brain lesions±aphasia. We compared their performance to an age- and education-matched control group and to 15 young controls (mean age 24±3 years). To investigate the influence of language deficits on test performance, we compared the scores of our patients with and without aphasia. - Results: Our patients were less accurate than the matched controls on the Tomato and Tuna Test, though not slower. The Kissing and Dancing Test did not differentiate between patients and matched controls. Young controls performed better than patients on both tests. - Conclusions: We found no performance differences between our aphasic and nonaphasic patients, confirming our assumption that both tests measure action understanding without requiring intact language abilities. We recommend the “Tomato and Tuna Test” as a new nonverbal measure of action understanding that can reveal subtle deficits.